Implemenation of Child Friendly City Policy in Singkawang City in 2022-2023 Period - U. Tria Andari; Rahman Mulyawan; Novie Indrawati Sagita (Dinasti Research, 2025)
This study aims to analyze the implementation of the “Child Friendly City” policy in Singkawang City, which is a strategic initiative to create an environment that is safe, healthy, and supports the development of children as the nation's next generation. Using a qualitative approach, this study collected data through in-depth interviews, direct observation, and analysis of relevant documents to understand the perspectives of various stakeholders, including local government, civil society organizations, educational institutions, and children's communities. The results show that despite strong commitment from the government and cross-sector collaboration, the implementation of this policy still faces various challenges. These challenges include different priorities among actors, budget constraints, and a lack of public understanding of the concept of “Child Friendly City”. In addition, although a non-compliance reporting mechanism is in place, socialization of this mechanism still needs to be improved so that children feel more confident in conveying the problems they face. Thus, this research concludes that the successful implementation of the “Child Friendly City” policy in Singkawang is highly dependent on effective collaboration between all parties, as well as the need for targeted strategies to overcome existing challenges. Hopefully, with a more collaborative and transparent approach, all children, especially those from vulnerable groups, can benefit equally from this policy, thus creating a child-friendly environment and supporting their holistic well-being. This research provides recommendations to improve socialization and education about the policy, strengthen cross-sector collaboration, and increase children's participation in decision-making, in order to achieve the goal of creating Singkawang City as a child-friendly city.